Resilient supply chains in Malaysia's manufacturing sector: A comparative analysis of priority industries affected by COVID-19 - Azmi, Fadhlur Rahim; Mohd Sukri, Nursyahwani; Mahmud, Nurazree; Sundram, Veera Pandiyan Kaliani; Hasbullah, Nornajihah Nadia; Musa, Haslinda (SHPMedia Sdn Bhd, 2025)
The COVID-19 pandemic exposed vulnerabilities within global supply chains, with Malaysia’s manufacturing sector, a cornerstone of the nation’s economy, experiencing significant disruptions. This study explores the interplay between supply chain risk management (SCRM), supply chain resilience (SCR), and sustainability efforts (SE) within the context of Malaysia’s priority manufacturing sectors—namely aerospace, chemicals, electrical and electronics (E&E), pharmaceuticals, and medical devices. Employing a quantitative research approach, data were collected from 360 firms, and the hypothesized relationships were analyzed using structural equation modeling. The findings confirm that effective SCRM practices significantly enhance SCR across all sectors, with the E&E industry exhibiting the strongest relationship due to its reliance on globalized networks. Furthermore, SCR positively influences supply chain performance (SCP), highlighting its critical role in maintaining operational efficiency, delivery reliability, and customer satisfaction during disruptions. The study also reveals a nuanced moderating role of SE on the SCRM-SCR relationship, with significant effects observed in the aerospace sector, underscoring the sector-specific dynamics of resilience-building efforts. This research offers one of the first empirical assessments of these dynamics across Malaysia’s most strategic manufacturing industries, providing sector-specific insights aligned with the country’s New Industrial Master Plan 2030. The findings offer valuable guidance for Malaysian businesses and policymakers seeking to enhance supply chain robustness, sustainability, and competitive advantage in preparation for future disruptions.